Juvenile justice in the making - Tanenhaus, David Spinoza (Studies in crime and public policy., 2004)
Faith in childhood, and its corollary that separate courts are required for children because they are developmentally different from adults, appears to be vanishing in the USA. This book examines one of America's most influential legal inventions and its future.